Is Informal Financial Aid Good for Health? Evidence from Kyrgyzstan, a Low-Income Post-Socialist Nation in Eurasia. Issue 4 (28th August 2018) - Urbaeva, Jildyz; Jackson, Theodore; Park, Daejun
Abstract: The importance of social capital and economic advantage for health is well established in literature. The relationship between health and social capital through informal financial aid is less understood. Using representative data ( N = 7, 474), authors explored an association between informal financial aid and health satisfaction in Kyrgyzstan, a post-socialist low-income country in Eurasia. Multilevel modeling revealed significant associations between informal aid and health. Cross-level interactions between individual and neighborhood financial aid were also significantly associated with health satisfaction. The results suggest that (a) social capital is influenced by socioeconomic status of the person, and (b) paths between informal aid and health vary among individuals at different levels of socioeconomic structure. Authors conclude the article with a discussion of the implications for social work practice and policy to improve health outcomes for disadvantaged individuals.